MASS HOLIDAYS IN UKRAINE: FORMS AND POSSIBILITIES OF TRANSFORMATION (XIX –XХ CENTURIES) - Svitlana Kutsak (Культура і мистецтво у сучасному світі, 2019)
The aim of the research is to study the peculiarities of mass holidays in Ukraine at the turn of the 19th and 20th centuries and to analyse mass holidays` historical transformation and their components. Methodology of the research consists in the application of factual, analytical, comparative, historical and logical methods that provided an opportunity to highlight the historical components of Ukrainian mass holidays – archaic, preserved in folk ceremonies, Christian, social, and national and historical. The scientific novelty of the study is to classify mass holidays in Ukraine at the turn of the XIX–XX centuries. The general connection of a mass holiday with the fundamental principles of human existence is shown, which provides a high level of its consolidating possibilities. Conclusions. In Ukraine at the turn of the XIX–XX centuries, four groups of mass holidays were popular: folk (archaic) rituals, religious-Christian rituals, and social imperial holidays, combined with mass festivals, and national historical-oriented mass holidays.